Looking for cosmic neutrino background - Yanagisawa, Chiaki (Frontiers in Physics, 2014)
Since the discovery of neutrino oscillation in atmospheric neutrinos by the Super-Kamiokande experiment in 1998, study of neutrinos has been one of exciting fields in high-energy physics. All the mixing angles were measured. Quests for 1) measurements of the remaining parameters, the lightest neutrino mass, the CP violating phase(s), and the sign of mass splitting between the mass eigenstates m3 and m1, and 2) better measurements to determine whether the mixing angle theta23 is less than pi/4, are in progress in a well-controlled manner. Determining the nature of neutrinos, whether they are Dirac or Majorana particles is also in progress with continuous improvement. On the other hand, although the ideas of detecting cosmic neutrino background have been discussed since 1960s, there has not been a serious concerted effort to achieve this goal. One of the reasons is that it is extremely difficult to detect such low energy neutrinos from the Big Bang. While there has been tremendous accumulation of information on Cosmic Microwave Background since its discovery in 1965, there is no direct evidence for Cosmic Neutrino Background. The importance of detecting Cosmic Neutrino Background is that, although detailed studies of Big Bang Nucleosynthesis and Cosmic Microwave Background give information of the early Universe at a few minutes old and 300 k years old, respectively, observation of Cosmic Neutrino Background allows us to study the early Universe at 1 sec old. This article reviews progress made in the past 50 years on detection methods of Cosmic Neutrino Background.